Pendidikan Seni Budaya dan Prakarya (SBdP) Sebagai Strategi Intervensi Umum bagi Anak Berkebutuhan Khusus - Lia Mareza (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
Art education can shape an individual's mental character, socio cultural personality, creativity and intellectual. Cultural art education is not only as a means of developing the knowledge and skills but as a general intervention strategies for children with special needs that based on socio-cultural. cultural arts and craft education has a uniqueness, significance and usefulness through activities to create, to appreciate and to express, so that children have role in the development of cognitive, affective and psychomotor than as aspects of catharsis in channeling the emotions as well as to stimulate active participation and improve the independence and directions on special needs childreen. The purpose of the use of intervention strategies was to help teachers knowing that the characteristic was associated with the competence of the child. This study was a qualitative research conducted in SD Negeri 1 Tanjung Purwokerto as one Inclussive School. Subject of research was principal, classroom teachers, assistant teachers, students and parents. The result of the research was intervention strategy can improve the ability of children. This was due to the orientation of making art more oriented to the modification process, the content of a work and the product.